Pengembangan Aplikasi Sistem Informasi Manajemen Laboratorium Teknik Sumberdaya Alam dan Mineral (TSAL) Fakultas Teknologi Pertanian Universitas Brawijaya - Gerwin Jonathan Henri; Denny Sagita Rusdianto; Eriq Muhammad Adams Jonemaro (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Mineral and Resource Engineering Laboratory is one of the laboratory that is built for giving some services that are needed to students and lecturers. The services can be for researching, loaning tools in laboratory, tools inventory, and also complaint services for a good quality in laboratory. Considering of high demands of those services, laboratory needs information system management that must be well-organized and well-structured, so optimum services can be reached. Model which used for software development that is used in this study is Waterfall. There are 4 processes such as requirement engineering, design system, implementation and testing. The results in requirement engineering are 57 functional requirements and 1 non functional requirement in the form of use case diagram and use case scenario. The results of design systems are sequence diagram, class diagram, user interface and pseudocode for implement. In implementation, technologies that are used are CodeIgniter framework with Hierarchial Model View Controller architecture and supported with web programming language such as HTML5, CSS3, JavaScript, PHP and MySQL. The results of unit testing is 100% valid for each case in the method, 100% valid for each case in integration module, 100% valid for 57 functional requirements and 100% valid for certain browsers such as Google Chrome and Mozilla Firefox.